Ethnopharmacological Approaches for Therapy of Jaundice: Part II. Highly Used Plant Species from Acanthaceae, Euphorbiaceae, Asteraceae, Combretaceae, and Fabaceae Families - Tewari, Devesh; Mocan, Andrei; Parvanov, Emil D.; Sah, Archana N.; Nabavi, Seyed M.; Huminiecki, Lukasz; Ma, Zheng Feei; Lee, Yeong Yeh; Horbańczuk, Jarosław O.; Atanasov, Atanas G. (Frontiers in Pharmacology, 2017)
In many developing countries, jaundice is the common symptom of hepatic diseases which are a major cause of mortality. The use of natural product-based therapies is very popular for such hepatic disorders. A great number of medicinal plants have been utilized for this purpose and some facilitated the discovery of active compounds which helped the development of new synthetic drugs against jaundice. However, more epidemiological studies and clinical trials are required for the practical implementation of the plant pharmacotherapy of jaundice. The focus of this second part of our review is on several of the most prominent plants used against jaundice identified in the analysis performed in the first part of the review viz. Andrographis paniculata (Burm.f.) Nees, Silybum marianum (L.) Gaertn, Terminalia chebula Retz., Glycyrrhiza glabra L. and some species of genus Phyllanthus. Furthermore, we discuss their physiological effects, biologically active ingredients, and the potential mechanisms of action. Some of the most important active ingredients were sylibin (also recommended by German commission), phyllanthin and andrographolide, whose action leads to bilirubin reduction and normalization of the levels of relevant serum enzymes indicative for the pathophysiological status of the liver.